THE WORLD ECONOMIC CRISIS AND ITS IMPACT ON THE SOCIOECONOMIC SITUATION IN KAZAKHSTAN - REVYAKIN, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2009)
The world financial crisis, which began with the collapse of the U.S. credit pyramid, is known to be the biggest crisis since the Great Depression.1 The first signs of the crisis appeared in the U.S. mortgage market in 20062 (housing loans were not being repaid), and shortly afterwards this market collapsed, triggering a global liquidity crisis. Housing prices in the U.S. plummeted, investments in housing construction fell, and the liquidity of the mortgage derivatives market began to decline. All of this took place against the background of a jump in credit spreads in money markets; the stocks of international companies plunged, and stock indexes fell significantly4 due to the bankruptcy of major financial institutions, primarily investment banks.5 Against the background of rising unemployment and tightening credit, the increase in U.S. consumer spending ceased in the second quarter of 2008 (for the first time since 1991).6 In the third quarter of 2008, investors withdrew 20 billion from investment funds in developing countries for fear that the crisis might cause a recession in these countries.7 The U.S. economy’s failure to cope with the escalating financial crisis was probably caused by the specific features of this economy